2001
DOI: 10.1073/pnas.041331498
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the endogenous smooth muscle myosin phosphatase-associated kinase

Abstract: Ca 2؉ sensitization of smooth muscle contraction involves inhibition of myosin light chain phosphatase (SMPP-1M) and enhanced myosin light chain phosphorylation. Inhibition of SMPP-1M is modulated through phosphorylation of the myosin targeting subunit (MYPT1) by either Rho-associated kinase (ROK) or an unknown SMPP-1M-associated kinase. Activated ROK is predominantly membrane-associated and its putative substrate, SMPP-1M, is mainly myofibrillar-associated. This raises a conundrum about the mechanism of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
250
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 201 publications
(257 citation statements)
references
References 33 publications
6
250
0
1
Order By: Relevance
“…Recently, it was found that ZIP kinase phosphorylates the regulatory light chain (MLC 20 ) of smooth muscle myosin [5,6]. This finding raised a possibility that ZIP kinase plays a role in cell contractile activity since the function of smooth muscle and non-muscle myosin is regulated by the phosphorylation of its MLC 20 [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, it was found that ZIP kinase phosphorylates the regulatory light chain (MLC 20 ) of smooth muscle myosin [5,6]. This finding raised a possibility that ZIP kinase plays a role in cell contractile activity since the function of smooth muscle and non-muscle myosin is regulated by the phosphorylation of its MLC 20 [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is known that MLC 20 is also phosphorylated at Thr18 in addition to Ser19 [10,11], which stabilizes the formation of myosin filaments and the myosin phosphorylated at both sites tends to form large thick filaments [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations